The Influence of Loyalty and Productivity on Employee Performance PT. Kreasindo Abadimas Medan Partners - Erika Erika (International Journal of Management Research and Economics, 2024)
Mitra Kreasindo Abadimas is a private company engaged in the sale and purchase of spare parts and machine repair services that has been operating since 2017. In its operational activities, the company experiences problems and problems that have not been resolved, namely disruption of employee performance due to lack of time to meet needs. The employee and the company are only asked to work continuously. Problems that allegedly cause poor employee performance in company operations are employee loyalty and low employee productivity. Simultaneous hypothesis test results show that simultaneously, loyalty and work productivity have a positive and significant effect on employee performance at PT. Kreasindo Abadimas Partners. The result of partial hypothesis test shows that partially, each variable of loyalty and work productivity has a positive and significant effect on employee performance at PT. Kreasindo Abadimas Partners.